2013
DOI: 10.1111/ajop.12005
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and addressing mental health risks and problems in primary care pediatric settings: A model to promote developmental and cultural competence.

Abstract: Young children, particularly uninsured children of color, suffer from mental health disturbances at rates similar to older children and adults, yet they have higher rates of unmet needs. To address unmet needs, efforts to identify mental health problems in primary care pediatric settings have grown in recent years, thanks in large part to expanded screening efforts. Yet, health disparities in early detection remain. Enhancing understanding of how early childhood mental health problems can be identified and add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
3
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 102 publications
2
44
3
6
Order By: Relevance
“…This challenge poses logistical and financial challenges to staff who are unable to effectively plan for the number of attendees, especially in the underresourced clinics that often serve low-income families; providers have limited time and resources to work on recruitment and often cannot bill for time spent on recruitment. Models of help-seeking behaviors suggest that an individual must first recognize that a problem exists before taking action to seek help (Godoy and Carter 2013); yet for prevention programs, recruitment is made especially challenging by the fact that there may not yet be an apparent problem. Other research has shown that thinking about seeking help mediates the association between parent appraisals of child problems and seeking help (Godoy et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This challenge poses logistical and financial challenges to staff who are unable to effectively plan for the number of attendees, especially in the underresourced clinics that often serve low-income families; providers have limited time and resources to work on recruitment and often cannot bill for time spent on recruitment. Models of help-seeking behaviors suggest that an individual must first recognize that a problem exists before taking action to seek help (Godoy and Carter 2013); yet for prevention programs, recruitment is made especially challenging by the fact that there may not yet be an apparent problem. Other research has shown that thinking about seeking help mediates the association between parent appraisals of child problems and seeking help (Godoy et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical models of help-seeking behaviors postulate that parent appraisals of child problems are a central force behind the decision to seek help (Godoy and Carter 2013). Parent decisions to engage in services represent a process marked by several steps, including identifying a problem and ''thinking about'' seeking help before engaging (Godoy et al 2014).…”
Section: Interventions To Enhance Parent Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…time, convenience and childcare burden) vs. benefits of such help, as well as the occurrence of catalysts, or triggering events (e.g. child entry into school, discussing child problems with a teacher, receiving an invitation to an intervention programme) affect parents' likelihood of obtaining such services for their young children (Godoy and Carter 2013). Starting Strong's presence in the school setting, during a crucial transition point, visible and accessible to all families at the school, with convenient times and child-care provided, may resolve some of these important barriers to help-seeking for parents of young children.…”
Section: Discussionmentioning
confidence: 99%
“…3 These shortcomings stem from a number of systemic and practice-level barriers including insufficient training, practical resources, time required to administer and score standardized instruments, guidance interpreting results, and options for referring children identified as needing mental health services. 4 The current study examines implementation of a computerized algorithmic support tool that facilitates screening and assessment of depression and anxiety in pediatric primary care and provides referral and treatment guidance. The algorithm incorporates standardized, psychometrically sound screening and next level assessment instruments for detecting clinically significant pediatric depression and anxiety.…”
Section: Brief Reportmentioning
confidence: 99%